2019
DOI: 10.6060/ivkkt.20196210.6046
|View full text |Cite
|
Sign up to set email alerts
|

ON MECHANISMS OF OXYGEN INFLUENCE ON GAS-PHASE PARAMETERS AND SILICON REACTIVE-ION ETCHING KINETICS IN HBr + Cl2 + O2 PLASMA

Abstract: The effects of both HBr/O2 and Cl2/O2 mixing ratios in HBr+Cl2+O2 gas mixture on plasma parameters, steady-state densities of active species and Si etching kinetics were studied under the typical conditions of reactive ion etching process: total gas pressure (p = 10 mTorr), input power (W = 500 W), bias power (Wdc = 200 W). The data on internal plasma parameters and plasma chemistry were obtained using a combination of Langmuir probe diagnostics and 0-dimensional (global) plasma modeling. It was found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…At the same time, the decreasing tendency for the ion bombardment energy appears to be weaker compared with the growth of ion flux. As results, one can obtain an increase in the ion bombardment intensity toward Ar-rich plasmas, as it follows from the change of (Mii) 1/2 + [10,11,19] (Fig. 1(c)).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…At the same time, the decreasing tendency for the ion bombardment energy appears to be weaker compared with the growth of ion flux. As results, one can obtain an increase in the ion bombardment intensity toward Ar-rich plasmas, as it follows from the change of (Mii) 1/2 + [10,11,19] (Fig. 1(c)).…”
Section: Resultsmentioning
confidence: 58%
“…Therefore, the difference between corresponding sputtering yields seems to be lower than that for effective reaction probabilities. In earlier works, it was shown that the experimentally obtained RIE rate, R, represents the combination of two summands, such as the rate of physical sputtering Rphys (since under typical RIE conditions the ion bombardment energy exceeds the sputtering threshold for etched material) and the rate of ion-assisted chemical reaction Rchem [10,11,22]. In order to evaluate contributions of these etching pathways, we measured SiO2 and Si3N4 etching rates in pure Ar plasma Rphys,Ar, calculate corresponding sputtering yields as YS,Ar = = Rphys,Ar/+ ( 0.03 for both SiO2 and Si3N4 at ion energy of 230 eV) and then, determined actual sputtering yields for HBr + Ar plasma as YS = YS,Ar(mi/mAr) 1/2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) [4,28,29]. Thus, reducing the etching rate with growth can take place with the dominance of both chemical and physical etching mechanisms.…”
Section: Plasma Simulationmentioning
confidence: 99%